A 2-oxa-spiro[5.4]decane scaffold displays neurotrophic, neurogenic and anti-neuroinflammatory activities with high potential for development as a versatile CNS therapeutic - Pranav Chintamani Joshi (Nature Portfolio, 2017)
Abstract Following our recent discovery of a new scaffold exhibiting significant neurotrophic and neurogenic activities, a structurally tweaked analogue, embodying a 2-oxa-spiro [5.4]decane framework, has been conceptualised and found to be more potent and versatile. It exhibits enhanced neurotrophic and neurogenic action in in vitro, ex vivo and in vivo models and also shows robust neuroprotection in mouse acute cerebral stroke model. The observed attributes are traceable to the predominant activation of the TrkB-PI3K-AKT-CREB pathway. In addition, it also exhibits remarkable anti-neuroinflammatory activity by concurrently down-regulating pro-inflammatory cytokines IL-1α and IL-6, thereby providing a unique molecule with a trinity of neuroactivities, i.e. neurotrophic, neurogenic and anti-inflammatory. The new chemical entity disclosed here has the potential to be advanced as a versatile therapeutic molecule to treat stroke, depression, and possibly other neuropsychiatric disorders associated with attenuated neurotrophic/ neurogenic activity, together with heightened neuroinflammation.